EIB Working Papers 2019/06 - Promoting energy audits - Ravillard, Pauline; Brutscher, Philipp-Bastian (European Investment Bank, 2021)
Energy audits are key to increase investments in energy efficiency This paper assesses the effectiveness of policy interventions in promoting energy audits by relying on evidence from a unique experiment. The findings of the experiment allow us to quantify by how much the probability that firms invest in energy audits increases, as the policy mix changes.